Development of Islamic Religious Education Learning Based on Total Quality Management at Salam Berkarya - Jailani, Mohammad (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to develop Islamic Religious Education (IRE) learning based on Total Quality Management (TQM) at Salam Berkarya School. The main objective of this research is to enhance the quality of IRE learning through the application of TQM principles. The research method employed is action research, involving the development and implementation of TQM-based learning in the IRE subject. The findings indicate that the development of TQM-based IRE learning at Salam Berkarya School has a positive impact on the quality of learning. By designing a relevant curriculum, using interactive teaching methods, providing accurate assessments, and integrating religious values into the learning process, students can better comprehend and internalize Islamic teachings. Additionally, teachers have clear guidelines for effective teaching, and the school is able to optimize available resources. This research contributes to the development of IRE teaching methods that focus on improving quality, character development, and the application of religious values in daily life. Furthermore, this study offers practical guidance for teachers and schools to adopt the TQM approach in the IRE learning process. It is hoped that the results of this research can serve as a reference for other schools to enhance IRE learning and produce a generation that comprehends and practices the teachings of Islam effectively.